2016
DOI: 10.3791/54062
|View full text |Cite
|
Sign up to set email alerts
|

Promoting 3-D Aggregation of FACS Purified Thymic Epithelial Cells with EAK 16-II/EAKIIH6 Self-assembling Hydrogel

Abstract: Thymus involution, associated with aging or pathological insults, results in diminished output of mature T-cells. Restoring the function of a failing thymus is crucial to maintain effective T cell-mediated acquired immune response against invading pathogens. However, thymus regeneration and revitalization proved to be challenging, largely due to the difficulties of reproducing the unique 3D microenvironment of the thymic stroma that is critical for the survival and function of thymic epithelial cells (TECs). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…[ 96 ] To regenerate the unique 3D cell microenvironment of the thymic stroma, EAK16‐II peptide hydrogel promotes the thymic epithelial cells (TECs) to form 3D cell aggregates. [ 97 ] Similar to PuraMatrix hydrogel, the functionalized characteristics are reported in EAK16‐II peptide hydrogel as well. EAK16‐II peptide with six histidine residues (His‐tags) can self‐sort or coassemble into stable β‐sheet structures to achieve in situ self‐gelling nanomaterials.…”
Section: Diverse Self‐assembling Peptide Hydrogels and Their Applicatmentioning
confidence: 75%
“…[ 96 ] To regenerate the unique 3D cell microenvironment of the thymic stroma, EAK16‐II peptide hydrogel promotes the thymic epithelial cells (TECs) to form 3D cell aggregates. [ 97 ] Similar to PuraMatrix hydrogel, the functionalized characteristics are reported in EAK16‐II peptide hydrogel as well. EAK16‐II peptide with six histidine residues (His‐tags) can self‐sort or coassemble into stable β‐sheet structures to achieve in situ self‐gelling nanomaterials.…”
Section: Diverse Self‐assembling Peptide Hydrogels and Their Applicatmentioning
confidence: 75%
“…Previously, we have functionalized EAK fibrillar gels and coacervates using a co‐assembly approach. [ 10,11,27–30 ] We showed that peptidic affinity domains appended with the EAK sequence can be incorporated into the fibrillar matrices, resulting in composites by which antibody molecules can be captured. Using this general approach, we have engineered His‐tags, protein G ( Streptococcus ), and subunit protein A ( Staphylococcus ) for displaying immunoglobulin G (IgG) indirectly or directly via interactions with the Fc regions of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Using this general approach, we have engineered His‐tags, protein G ( Streptococcus ), and subunit protein A ( Staphylococcus ) for displaying immunoglobulin G (IgG) indirectly or directly via interactions with the Fc regions of antibodies. [ 27,28,30 ] From these platforms we have constructed gels and coacervates for localizing antibodies in tumors and in skin allografts, and as scaffolds for constructing thymic organoids in vitro and in vivo. [ 10,11,28 ] These systems of proteins and/or cells can be administered with conventional syringes; they do not elicit local inflammation or acute toxicities in mice after repeated subcutaneous injections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique pattern of alternating negative and positive charges interspersed with a small hydrophobic residue in AEAEAKAKAEAEAKAK (referred to as EAK hereafter) drives the peptide to undergo sol-gel phase transition, forming cross-linking β-fibrils in the presence of salt. We have used a coassembly strategy to engineer Fc-binding function into the fibrillar materials by mixing EAK with another EAK-containing peptide appended with a His-tag (EAKH6) or the single-chain variable fragment dL5 (dL5_EAK) [4][5][6][7][8][9][10][11] . These Fc-binding composites can concentrate IgG antibodies locally in vivo.…”
Section: Introductionmentioning
confidence: 99%